Strategi Pengembangan Bank Sampah Sahdu Skala Kelurahan di Desa Tanimulya Kabupaten Bandung Barat - Yulianti Pratama; Muhammad Rizki Kurniawan (Jurnal Serambi Engineering, 2022)
Out of four waste banks in the Tanimulya Village, Sahdu Waste Bank is the only proper waste bank in operation. Based on the 2019 West Bandung District’s Environmental Agency (Dinas Lingkungan Hidup Kebersihan) Strategic Plan, which stated the target in 2022, that it needs to reduce 10%, from the current 8% reduction of the waste generation through the solid waste management and waste bank facilites, prior to the landfill. One of the efforts that can be done is through the development of the Sahdu Waste Bank from the hamlet scale to the urban village scale by using the Waste Bank Indexing Method. Assessing the existing condition with the waste bank index, identification and compiling the recommendation towards parameters that need improvement. Based on the results of the assessment, a score of 53.2 (out of 100, and is considered as fairly good category), reveals 14 sub indicator that can be improved, which consist of 6 Sub Indicator of Management System, 6 Sub Indicator of Operational System, and 2 Sub Indicator of Waste Bank Facility. The value of the Sahdu Waste Bank can be increased to 88.3 (out of 100, and is considered as very good), which generates the reduction of 266.67% of waste, equal to 4 ton/month from 150 kg/month. That would make Sahdu Waste Bank contributes 1.6% from the reduction target of 10% for the West Bandung District waste.